Republic of Estonia : Staff Report for the 2000 Article IV Consultation and First Review Under the Stand-By Arrangement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The economic recovery seems to be firmly established, supported by strengthened domestic private demand. The Bank of Estonia (BoE) is committed to maintaining the currency board until the euro becomes Estonia's official currency. The compliance with the Basel Core Principles (BCP) has improved and is now high. Monetary and financial policies are transparent. Financial sector assessment program recommendations have been integrated into the government's work program. Good progress is being made in the implementation of the structural reform agenda, including the privatization of major infrastructure companies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet